Recent Progress in Carbon-Based Buffer Layers for Polymer Solar Cells - Nguyen, Thang Phan (Polymers (Basel), 2019)
Carbon-based materials are promising candidates as charge transport layers in various optoelectronic devices and have been applied to enhance the performance and stability of such devices. In this paper, we provide an overview of the most contemporary strategies that use carbon-based materials including graphene, graphene oxide, carbon nanotubes, carbon quantum dots, and graphitic carbon nitride as buffer layers in polymer solar cells (PSCs). The crucial parameters that regulate the performance of carbon-based buffer layers are highlighted and discussed in detail. Furthermore, the performances of recently developed carbon-based materials as hole and electron transport layers in PSCs compared with those of commercially available hole/electron transport layers are evaluated. Finally, we elaborate on the remaining challenges and future directions for the development of carbon-based buffer layers to achieve high-efficiency and high-stability PSCs.